Effectiveness of mindfulness – based acceptance and commitment therapy counseling on the self-acceptance of children in conflict with the law: a single-subject experimental study - Nurul Aya Mufidah Rahmat Rahmat; Sahril Buchori; M. Amirllah; Syahril Syahril (JPGI (Jurnal Penelitian Guru Indonesia), 2026)
Children in Conflict with the Law (CICL) are prone to low self-acceptance due to stigma, guilt, and emotional pressure during legal proceedings. Given that CICL often experience cognitive fusion with negative self-labels and engage in avoidant coping, Acceptance and Commitment Therapy (ACT) was selected for its emphasis on psychological flexibility through mindfulness, acceptance, cognitive defusion, and values-based committed action. This study aims to analyze changes in Subject N's self-acceptance through mindfulness-based ACT. The quantitative method uses an A-B-A Single Subject Research (SSR) design, consisting of baseline A1, intervention B, and post-intervention A2. The subject is a CICL identified as N with low self-acceptance. The intervention integrates six core ACT processes with mindfulness exercises, delivered over seven sessions of 40 minutes each. Data from questionnaires and structured observations measure four aspects: awareness of vulnerability, balanced self-perception, separation of behavior from self-worth, and unconditional self-acceptance. Data were analyzed visually. Results showed a significant increase from 10 (low) at A1 to 31 (high) at A2. The 0% overlap confirms changes occurred due to the intervention. Thus, mindfulness-based ACT effectively improves Subject N's self-acceptance and can be an adaptive intervention for CICL with low self-acceptance.